2003
DOI: 10.1038/sj.ejhg.5200964
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the diagnosis of malignant hyperthermia susceptibility: How confident can we be of genetic testing?

Abstract: Malignant hyperthermia (MH) is a condition that manifests in susceptible individuals only on exposure to certain anaesthetic agents. Although genetically heterogeneous, mutations in the RYR1 gene (19q13.1) are associated with the majority of reported MH cases. Guidelines for the genetic diagnosis for MH susceptibility have recently been introduced by the European MH Group (EMHG). These are designed to supplement the muscle biopsy testing procedure, the in vitro contracture test (IVCT), which has been the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 33 publications
1
61
2
Order By: Relevance
“…However, since the large size of the RYR1 gene (106 exons) makes genetic analysis very laborious and expensive, mutation screening is preferentially performed only in those exons where known mutations are clustered [Barone et al, 1999;Brandt et al, 1999;Lynch et al, 1999;Galli et al, 2002;Robinson et al, 2003;Tilgen et al, 2003;Tammaro et al, 2003;Sambuughin et al, 2001]. This approach has resulted in the identification of mutations in the RYR1 gene in approximately 30-50% of the probands identified as MHS at the in vitro contraction test (IVCT) [European Malignant hyperpyrexia Group, 1984;Robinson et al, 2003], while analysis of the entire RYR1 coding sequence is only rarely performed [Sambuughin et al, 2005;Monnier et al, 2005]. Overall, this may generate a bias that favors extensive identification of mutations in specific areas of the RYR1 gene while limiting the identification of additional regions where mutations may also occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the large size of the RYR1 gene (106 exons) makes genetic analysis very laborious and expensive, mutation screening is preferentially performed only in those exons where known mutations are clustered [Barone et al, 1999;Brandt et al, 1999;Lynch et al, 1999;Galli et al, 2002;Robinson et al, 2003;Tilgen et al, 2003;Tammaro et al, 2003;Sambuughin et al, 2001]. This approach has resulted in the identification of mutations in the RYR1 gene in approximately 30-50% of the probands identified as MHS at the in vitro contraction test (IVCT) [European Malignant hyperpyrexia Group, 1984;Robinson et al, 2003], while analysis of the entire RYR1 coding sequence is only rarely performed [Sambuughin et al, 2005;Monnier et al, 2005]. Overall, this may generate a bias that favors extensive identification of mutations in specific areas of the RYR1 gene while limiting the identification of additional regions where mutations may also occur.…”
Section: Introductionmentioning
confidence: 99%
“…Discordance between CHCT and genetic studies has already been reported (26)(27)(28)(29)(30), indicating that some familial mutations are not found in some MHS members of the family. It is also possible that this discordant individual has another mutation in another part of RYR1 not analyzed or in another gene related to MH (4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic research into the condition implicated the ryanodine receptor gene (RYR1) located on chromosome 19 [4,5], and DNA testing is now used routinely for diagnosis before muscle biopsy when a familial RYR1 mutation is known [6]. However, the number and nature of RYR1 variants [7] and the increasingly perceived complexity of the genetics of MH [8][9][10] , potassium concentration 6 mmol.l )1 and creatine kinase concentration 29 900 IU.l . Later, he developed disseminated intravascular coagulation with haematuria and died 12 h after the initial episode.…”
Section: Malignant Hyperthermia In Indiamentioning
confidence: 99%